Three Solar Irradiance Proxies for Aperture Photoelectron Detections in Top‐Hat ESAs Coated With Ebonol‐C. Issue 12 (23rd December 2021) - da Silva, D.; Gershman, D.; Barrie, A.; Elkington, S.; Li, X.; Kirk, M.; Giles, B.; Avanov, L.; Shuster, J.; Paterson, B.; Schiff, C.; Chen, L. J.
Abstract: Decades after the introduction of top‐hat electrostatic analyzers (ESAs) to experimental space plasma physics, photoelectron noise in apertures of low‐energy electron instruments continues to be an issue in instrument performance. The photoelectrons at each portion of measured phase space distribution can be mapped through laboratory and in‐flight testing, and have been for many missions. In flight, the photoelectrons are a response to dynamic solar EUV spectral intensities which vary over the course of a solar cycle and even within a solar rotation. This paper outlines three solar irradiance proxies that can be used to scale a map of photo‐electron locations in phase space in order to account for dynamic solar activity. These proxies apply to top‐hat ESAs coated with Ebonol‐C (the most common coating) used by missions such as MMS, Solar Orbiter, the Van Allen Probes, and Juno. These proxies are discovered by searching possible wavelengths for correlation with an independent algorithm for MMS/FPI (Magnetospheric Multiscale Mission/Fast Plasma Instrument) which automatically determines the scaling factor. The three wavelengths that serve as viable proxies are found to be: 17.5, 30.5, and 37.5 nm. Plain Language Summary: Space instruments measuring electron distributions have a noise source originating from photoelectrons caused by solar EUV. The photoelectrons are closely associated with the spectrum of solar EUV, which is dynamic over a solar cycle and even within a solar rotation. This work shows that three wavelengths (17.5, 30.5, and 37.5 nm) serve as good proxies for the entire relevant EUV spectrum that generates the noise associated with the photoelectrons. These proxy wavelengths work well when the instrument is a top‐hat electrostatic analyzer (ESA) coated with Ebonol‐C, which is a commonly used coating. Key Points: Scale factors to adjust a background photoelectron map for low‐energy top‐hat electron ESAs should be updated multiple times per month A method is presented to use proxy spectral irradiances to estimate the scale factor Three wavelengths suitable for use as proxies with this method are found